Guidelines for the management of pregnant women with obesity: A systematic review. (14th January 2020) - Simon, Alexandre; Pratt, Misty; Hutton, Brian; Skidmore, Becky; Fakhraei, Romina; Rybak, Natalie; Corsi, Daniel J.; Walker, Mark; Velez, Maria P.; Smith, Graeme N.; Gaudet, Laura M.
Summary: Multiple clinical practice guidelines (CPGs) have been established for pregnant women with obesity. The quality and consistency of recommendations remain unknown. The objective of this study is to conduct a systematic review to synthesize and appraise evidence from CPGs, available worldwide, for pregnant women affected by obesity. An experienced information specialist performed a rigorous search of the literature, searching MEDLINE, Embase, grey literature, and guideline registries to locate CPGs that reported on pregnancy care relating to obesity. CPGs related to antenatal care of pregnant women with obesity (pre‐pregnancy body mass index [BMI] ≥ 30 kg/m 2 ) in low‐risk (eg, care provider = family physician or midwife) or high‐risk settings (eg, obstetrician or maternal fetal medicine) were included. CPGs were appraised for quality with independent data collection by two raters. Information was categorized into five domains: preconception care. care during pregnancy, diet and exercise during pregnancy, care immediately before, during, and after delivery, and postpartum care. The literature search yielded 2614 unique citations. Following screening of abstracts and full texts, 32 CPGs were included, with quality ranging between 0 and 100 on the AGREE II tool. The strongest evidence related to nutritional advice, exercise, and pregnancy risk counselling. Guidance was limited for timing of screening tests, antenatal visits and delivery, ideal postpartum care, and management of adverse pregnancy outcomes. Most guidelines in this population are not evidence based. Research is needed to bridge knowledge gaps pertaining to fetal antenatal surveillance, management of adverse outcomes and postpartum care, and enhance consistency across CPGs.